Effect of Extracts from Azadiraachta indica and Trichilia pallida on Control to Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) on Maize. - Conceschi, Marcos R.; Ansante, Thiago Felipe; Mazzonetto, Fábio; Vendramim, José Djair; Sossai, Vera Lúcia Monelli; Pizetta, Luiz Carlos; Corbani, Renato Zapparoli (BioAssay, 2011)
Insecticides plants have been studied as an alternative to control of Spodoptera frugiperda, important pest on maize. This work aimed to evaluate the effectiveness of the aqueous extract of Azadirachta indica (EAI) and Trichilia pallida (ETP) on S. frugiperda in fed corn leaves (hybrid ZB 710) on different forms of application. It was used pieces of leaves of 16 cm2, immersed by 4 seconds or sprayed at concentration of 5%, and thus transferred to glass tubes being exchanged every 24 hours. The biological variables assessed were daily mortality, larval weight, measurements of head capsule and lengths on the 5o day of evaluation. The design was wholly randomized, composed of seven treatments (control, leaves immersed in (EAI), caterpillars sprayed with (EAI), leaves immersed and caterpillars sprayed with (EAI), leaves immersed in ETP, caterpillars sprayed with ETP, caterpillars sprayed and leaves immersed in ETP), with 40 repetitions per treatment. The data were submitted to the Log-rank test, Wilcoxon and Tarone-Ware for comparison of survival curves, using the tecnique multivaried (Cluster) and the connection method by neighboring more distant and Euclidean distance and also the Spearman's correlation and Bonferroni’s method for the variables analysed on the five day. Results based on survival analysis and multivariate statistics, we found out that the mortality of larvae and the values of larval weight and length, and of head capsule width were significantly affected when subjected to treatment with submerged leaves and caterpillars sprayed with extract from A. indica and with leaves immersed in this extract.